Accuracy improvement for linear tetrahedral finite element by means of virtual mesh refinement / Sugeng Waluyo - Waluyo, Sugeng (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2015)
This paper offers a new strategy to improve accuracy on deformation field of linear 4-node tetrahedral finite elements (FE) commonly used in computer aided engineering (CAE) software by means of virtual mesh refinement (VMR). Here, the improvement is achieved by embodying additional virtual strain energy to the FE instead of using physical mesh refinement in particular domains. In this early development only total strain energy of elements in the domains after simulation is used to assess convergence during the VMR process. Finally, two benchmarking studies, i.e., classical cantilever beam and thin shell torsion, are used to test the ability of the method to solve shear dominated problems in large and small deformation, respectively. From the studies, improvements in the deformation accuracy by order of 200% are observed.